Innovative study on chalcopyrite flotation efficiency with xanthate and ester collectors blend using response surface methodology (B.B.D): towards sustainability - Imkong Rathi; Shravan Kumar (Scientific Reports)
Abstract The Malanjkhand chalcopyrite deposit, India’s primary copper ore producer, has potential for enhanced flotation performance. This study employs standard flotation experiments using a mechanical cell, integrating a conventional collecting agent with a novel ester-based collector blend. A three-factor, three-level Box-Behnken design systematically evaluated experimental parameters, analysed using ANOVA, cubic plots, response surface methodologies. Investigation examines the effects-interactions of three key parameters in chalcopyrite flotation: dosages of sodium silicate (depressant), (SIPX- collector) and acetoacetic acid n-octyl ester (AoE) (co-collector/modifier). Both high-grade (HG) and low-grade (LG) ore samples were tested to compare process outcomes. Results showed that incorporating AoE with optimized SIPX dosages increased copper grade by at least 15%, with favorable recovery rates. For the HG sample, optimal conditions for a 93.64% recovery were 0.001 kg/t sodium silicate, 0.005 kg/t SIPX, and 0.00125 kg/t AoE. Achieve an optimized grade of 3%, a 78.1% increase from the feed sample, the ideal conditions were 0.00175 kg/t sodium silicate, 0.005 kg/t SIPX, and 0.0005 kg/t AoE for the HG sample. Validation experiments confirmed the results, aligning well with statistical model predictions. Calculated (SPI) value of 0.1241 capita kg-1 falls within the desirable range of 0 to 1, indicating the reliability-accuracy of the outcomes.